A bioprinted complex tissue model for myotendinous junction with biochemical and biophysical cues - Won Jin Kim; Geun Hyung Kim (Wiley, 2022)
Abstract In the musculoskeletal system, the myotendinous junction (MTJ) is optimally designed from the aspect of force transmission generated from a muscle through a tendon onto the bone to induce movement. Although the MTJ is a key complex tissue in force transmission, the realistic fabrication, and formation of complex tissues can be limited. To obtain the MTJ construct, we prepared two bioinks, muscle‐ and tendon‐derived decellularized extracellular matrix (dECM), which can induce myogenic and tenogenic differentiation of human adipose‐derived stem cells (hASCs). By using a modified bioprinting process supplemented with a nozzle consisting of a single‐core channel and double‐sheath channels, we can achieve three different types of MTJ units, composed of muscle, tendon, and interface zones. Our results indicated that the bioprinted dECM‐based constructs induced hASCs to myogenic and tenogenic differentiation. In addition, a significantly higher MTJ‐associated gene expression was detected at the MTJ interface with a cell‐mixing zone than in the other interface models. Based on the results, the bioprinted MTJ model can be a potential platform for understanding the interaction between muscle and tendon cells, and even the bioprinting method can be extensively applied to obtain complex tissues.